Strategi Peningkatan Rata-Rata Lama Sekolah Melalui Alokasi Anggaran Bidang Pendidikan Di Kabupaten Bogor - Erik Harninta Putra; Falatehan, A. Faroby; Harianto, Harianto (JRB-Jurnal Riset Bisnis, 2023)
Human development emphasizes on enlarging people’s choices and improving their well-being. Education is a key to meet the goals of human development. It could be seen through Mean Years Schooling (MYS) as an indicator indicating education achievement of community. Bogor regency has a potential human resource dominated by productive age. However, their Mean Years Schooling is still under the Mean Years Schooling achievement of West Java Province and national level. The purpose of this research was to formulate a strategy in improving Mean Years Schooling in Bogor regency. This study used SWOT (Strengths, Weaknesses, Opportunities, Threats) and QSPM (Quantitative Strategic Planning Matrix) as analisis methods. There were seven alternative strategies formulated by SWOT analysis that then were prioritized using QSPM in order to obtain a priority strategy. It was finally determined that implementing a productive budget allocation on education development was the priority strategy for increasing Mean Years Schooling in Bogor Regency. Keywords: MYS, education development, SWOT, QSPM